MIR156-Targeted SPL9 Is Phosphorylated by SnRK2s and Interacts With ABI5 to Enhance ABA Responses in Arabidopsis - Dong, Huixue; Yan, Suli; Jing, Yexing; Yang, Ruizhen; Zhang, Yunwei; Zhou, Yun; Zhu, Yingfang; Sun, Jiaqiang (Frontiers in Plant Science, 2021)
The miR156-targeted SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factors play key roles in regulating plant development, but little is known about their function in abscisic acid (ABA) signaling. Here, we report that the miR156-targeted SPLs enhance ABA responses and contribute to the inhibition of pre-harvest sprouting. We find that SPL9 directly activates the expression of ABA responsive genes through binding to their promoters. SPL9 was further shown to physically interact with ABSCISIC ACID INSENSITIVE 5 (ABI5), a master transcription factor in ABA signaling, thus promoting its association with the promoters of ABA responsive genes. Furthermore, we reveal that the protein kinases SnRK2s interact with and phosphorylate SPL9, which is essential for its role in the activation of ABA responses. Together, our results disclose a SnRK2s-SPLs-ABI5 regulatory module in ABA signaling in Arabidopsis.